Macromolecular confinement of therapeutic protein in polymeric particles for controlled release: insulin as a case study - Luiz Henrique Guerreiro; Daniel da Silva; Wendell Girard-Dias; Camile Moreira Mascarenhas; Kildare Miranda; Mauro Sola-Penna; Eduardo Ricci Júnior; Luís Mauricio Trambaioli da Rocha e Lima (Universidade de São Paulo, 2017)
ABSTRACT Sustained release systems for therapeutic proteins have been widely studied targeting to improve the action of these drugs. Molecular entrapping of proteins is particularly challenging due to their conformational instability. We have developed a micro-structured poly-epsilon-caprolactone (PCL) particle system loaded with human insulin using a simple double-emulsion w/o/w method followed by solvent evaporation method. This formulation is comprised by spheric-shaped microparticles with average size of 10 micrometers. In vitro release showed a biphasic behavior such as a rapid release with about 50% of drug delivered within 2 hours and a sustained phase for up to 48 h. The subcutaneous administration of microencapsulated insulin showed a biphasic effect on glycemia in streptozotocin-induced diabetic mice, compatible with short and intermediate-acting behaviors, with first transition peak at about 2 h and the second phase exerting effect for up to 48h after s.c. administration. This study reveals that a simplified double-emulsion system results in biocompatible human-insulin-loaded PCL microparticles that might be used for further development of optimized sustained release formulations of insulin to be used in the restoration of hormonal levels.